X-ray observations of Kβ emission from medium Z He-like ions in C-Mod tokamak plasmas. (17th January 2018) - Rice, J E; Rosmej, F B; Cao, N; Chilenski, M; Howard, N T; Hubbard, A E; Hughes, J W; Irby, J H; Lin, Y; Rodriguez-Fernandez, P; Wolfe, S M; Wukitch, S J; et al.
Abstract: X-ray spectra of n = 3–1 transitions in He-like ions (and satellites) from calcium, argon and chlorine have been measured in the core of Alcator C-Mod tokamak plasmas using high wavelength resolution x-ray spectrometer systems. The intensity ratio of the intercombination line y 3 (1s3p 3 P1 –1s 2 1 S0 ) to the resonance line w 3 (1s3p 1 P1 –1s 2 1 S0 ) is found to be much larger than what is expected if collisional excitation out of the ground state is considered as the only population mechanism for the upper levels. This suggests that recombination and cascades from higher levels with n ≥ 4 are important. Modeling with the MARIA code is in good agreement with the observations, demonstrating the importance of recombination population of the upper level for y 3 . The intensity ratio y 3 / w 3 has been studied over a large range of core electron temperature and density, and radial position in the plasma. The observed ratio decreases with increasing T e, increases with increasing Z and is independent of n e, in agreement with modeling.